Proses Pelesepan Fonologi Pada Leksikon Bahasa Sumbawa Dialek Sumbawa Besar - Umar . (Journal Social and Humaniora, 2018)
The users of Sumbawa’s Besar dialect was used by many people in Sumbawa Regency. Almost Sumbawa region utilized Sumbawa’s Besar dialect in getting communication. In a general way, this language is utilized word-of-mouth deep gab everyday among the users in the society member whereas in writing form is still found sparse. In this study used qualitative method. Meanwhile, the result of data analysis which is sound disappearance pprocess that happening in Sumbawa’s Besar Dialect is Aferesis (sound disappearance on course startup), Sinkope (sound disappearance on course mean), and Apokope (sound disappearance on course final). This process happening on segment that do not accentual and in particular on homorgan’s sounds. And there is factor even its happening causative sound disappearance are divided as two which are non-linguistics and linguistics factor.